29.6k views
3 votes
Write the following equation in the general form Ax + By + C = 0. 2 x + y = 6 2x + y - 6 = 0 2x + y + 6 = 0 2x - y - 6 = 0

2 Answers

6 votes

2x + y - 6 = 0

given 2x + y = 6 ( subtract 6 from both sides )

2x + y - 6 = 0 ← in general form


User Jordan Messina
by
5.8k points
5 votes

Answer:

Option B

Explanation:

We have to write the equation in the general form

Ax + By + c = 0

Equation is 2x + y = 6

We subtract 6 on both the sides of the equation to convert in the standard form.

2x + y - 6 = 6 - 6

2x + y - 6 = 0

where A = 2

b = 1

and c = (-6)

Option B will be the answer.

User Ryan Francesconi
by
6.8k points